Nilai-Nilai Pendidikan Agama Islam dalam Tradisi Ari Ana Mahun Masyarakat Negeri Kilkoda Kabupaten Seram Bagian Timur - Ade Salma Renati Kasongat; Hermansyah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The purpose of this article is to explain the values ​​of Islamic religious education contained in the Ari Ana Mahun tradition in the people of Negeri Kilkoda, Gorom Island District, East Seram Regency. A unique tradition called Ari Ana Mahun or children's maulid is found in Negeri Kilkoda, Gorom Islands, East Seram Regency. Different from the usual commemoration of the Prophet Muhammad's birthday, this tradition is carried out 15 days before the month of Ramadan as a form of respect for children or family members who have died. The community believes that prayers and prepared food will make the spirits happy, as well as being a medium for maintaining Islamic cultural heritage. This tradition is carried out once a year and is passed down from generation to generation. In addition to being a form of respect, Ari Ana Mahun is a means of education for the community to preserve Islamic traditions and strengthen religious values. These values ​​are instilled from generation to generation so that the community maintains their cultural and spiritual identity. This paper aims to describe the values ​​of Islamic education contained in it. The research uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. Data analysis was conducted through the stages of collection, reduction, presentation, and drawing conclusions. The results indicate that this tradition involves determining the date, preparing traditional food, visiting graves, decorating the containers, reciting prayers together, giving alms to children, and planting a raung (a symbol of Islam) at the graves. The Islamic educational values ​​contained include monotheism, worship, morals, silaturahmi (silaturahmi), instilling religious values ​​from an early age, and preserving Islamic culture.